2014
DOI: 10.1042/bj20140712
|View full text |Cite
|
Sign up to set email alerts
|

The molecular regulation of Janus kinase (JAK) activation

Abstract: The Janus Kinase (JAK) family members serve essential roles as the intracellular signalling effectors of cytokine receptors. This family, comprising JAK1, JAK2, JAK3 and TYK2, was first described more than 20 years ago, but the complexities underlying their activation, regulation and pleiotropic signalling functions are still being explored. Here, we review the current knowledge of their physiological functions and the causative role of activating and inactivating JAK mutations in human diseases, including hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
223
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(228 citation statements)
references
References 165 publications
1
223
1
3
Order By: Relevance
“…TYK2 was identified in the pathway analysis described above, and it plays a critical role in the intracellular signaling of type I IFNs via phosphorylation and activation of STAT proteins (14). Of note, type I IFNs play an important role in several autoimmune IFNb (E and K), and CXCL10 (F and L) was measured in the supernatants by ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TYK2 was identified in the pathway analysis described above, and it plays a critical role in the intracellular signaling of type I IFNs via phosphorylation and activation of STAT proteins (14). Of note, type I IFNs play an important role in several autoimmune IFNb (E and K), and CXCL10 (F and L) was measured in the supernatants by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Ingenuity Pathway Analysis of the type 1 diabetes candidate genes expressed in human pancreatic b-cells identified as the three top canonical pathways "interferon signaling," "role of JAK1, JAK2 and TYK2 in IFN signaling," and "role of pattern recognition receptors in recognition of bacteria and virus." TYK2, a key regulator of IFN signaling (14), was listed in three out of the four top canonical pathways identified, namely, "interferon signaling," "role of JAK1, JAK2 and TYK2 in IFN signaling," and "Tec kinase signaling." Furthermore, and in line with a previous bioinformatics prediction (15), BLCLs obtained from patients with genotype AA of the TYK2 SNP rs2304256 (the variant protective against type 1 diabetes) showed a trend for less marked IFNa-induced STAT1 phosphorylation, as compared with patients with genotype CC (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the tyrosine phosphorylation of the members of the Janus family of kinases, including Jak1, Jak2, Jak3 and tyrosine kinase 2 (Tyk2), may be involved in the occurrence and development of prostate and breast cancer (9). Specifically, it has been demonstrated that Jak3 is involved in dendritic cell maturation and migration via the CCR7-mediated signaling pathway (10,11).…”
Section: Introductionmentioning
confidence: 99%